Celebrating 200 Years of Vuk's Dictionary (Golub Jašović, Vukovim tragom na Kosovu i Metohiji. K. Mitrovica: Faculty of Philosophy - City Library Vuk Karadžić, 2019) - Stefanović, Dušan R. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The article does not contain abstract.